PERANCANGAN VISUALISASI TATA URUTAN PERUNDANG-UNDANGAN DI INDONESIA (Information Technology and Telematics, 2014)
Abstract -Acourse musthave astatelawthatserves to regulate thelife of the nation citizens. Sosialition legislation currently done for example by utilizing the very rapid development of the Internet through websites / web owned by almost all government departments. Sosialition legislation linked to one another can be clarified with the visualization of the law so that people helped in the search. This study makes a system to visualize the hierarchy of legislation of law a inter related with each other. The information will be obtained by the user using the data structure java script language and using Json structure. To depiction visualization using graph methods. The data entered by the useras input (input)  will be processed and issued as output data(output) in the form of visualization describtion. This study resulted in a system that can give you an idea link ages between law so that it can be used in accordance with user requirements Keyword: Java Script, Json, Graph, Visualisasi, Undang-Undang